TEACHING ENGLISH AS AN INTERNATIONAL LANGUAGE BY INTRODUCING CULTURES AVAILABLE AROUND US - Tiur Simanjuntak (Politeknik Negeri Sriwijaya, 2010)
The concept of English as an international language means English is treated as a global means of communication. This concept shows that English has a various dialects influence by the first language or it refers to the array of varieties of English spoken throughout the world. Therefore the focus of having a good model in English speaking countries, but we can look around and see cultures available around us and integrate them into English language teaching. May studies have highlighted that inserting culture particularly target language culture in EFL class is necessary because language is considered as carrier of culture. Moreover, integrating local culture is also interesting because local culture is hands on, available any time around us; it isliterally spoken, and accessible; therefore it is not time consuming, it is cheaper and easier to be implemented. Moreover, it advances cooperative learning which improves independency and prepares students to live in globalized world. Viewed from teaching materials, local cultures is rich for its diversity and helps students to develop their identity by thinking about their own culture and by learning about others. Through differences or similarities, they establish an understanding that each of them is different, and understanding that each of them has a culture which is interesting and beneficial to look at.